Bargaining with Noisy Communication - Paolo Garella; Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
In this paper we show that in a bargaining situation the seller may not necessarily want to fully exploit communication possibilities. In the standard two-period bargaining model with one-sided incomplete information, the seller, who owns an indivisible good, makes oers which the buyer can either accept or reject. We ask whether the seller can prot from manipulating the communication mechanism by sending offers that reach the buyer with probability less than one (noisy communication). Noisy communication is a way to improve the seller's second period beliefs about the buyer's willingness to pay for the good and is therefore a way to "buy" commitment. We study the case of a discrete distribution of buyer's types and show that there exist equilibria with noisy communication when there are at least three different types of buyers.
Keywords: 330